The artificial intelligence revolution in the food industry: advances, challenges, and perspectives toward smart and sustainable food systems. A revolução da inteligência artificial na indústria alimentar: avanços, desafios e perspectivas para sistemas al (Ingeniería, Sostenibilidad y Sociedad, 2025)
The food industry faces growing challenges related to safety, sustainability, and efficiency. In this context, artificial intelligence (AI) emerges as a key technology to address these issues. This article critically reviews a series of recent advances in AI applications integrated with disruptive technologies in the food sector. Key areas identified include food safety, traceability, adulteration detection, smart packaging, consumer perception, and sustainability. The benefits highlighted include real-time monitoring, predictive analytics, and automation, while also pointing out challenges in interoperability, data governance, and social acceptance. Interdisciplinary research lines are suggested to advance toward smart and sustainable food systems.
Keywords: artificial intelligence; food safety; Industry 4.0; traceability; smart packaging; sustainability